The Rumphulus - Peterson, Joseph G. (Book collections on Project MUSE., 2020)
"Romulus was the founder of Rome; and those tossed outside the city-gate are not Romulus's children but the cast-offs living in hovels, the Rumphulus. The City is not Rome, but an American town; the outcasts don't know why they've been cast off into the woods and they don't know if they'll ever escape back into the town. But they've grown their beards long and when they can no longer stand it they howl like wolves, only they are not wolves but the stranded outcasts of the town howling in pain. They are the Rumphulus"--